Development and techno-economic analyses of a novel hydrogen production process via chemical looping. (13th August 2019) - Bahzad, Husain; Shah, Nilay; Dowell, Niall Mac; Boot-Handford, Matthew; Soltani, Salman Masoudi; Ho, Minh; Fennell, Paul S.
Abstract: In this work, a novel hydrogen production process (Integrated Chemical Looping Water Splitting "ICLWS") has been developed. The modelled process has been optimised via heat integration between the main process units. The effects of the key process variables ( i.e. the oxygen carrier-to-fuel ratio, steam flow rate and discharged gas temperature) on the behaviour of the reducer and oxidiser reactors were investigated. The thermal and exergy efficiencies of the process were studied and compared against a conventional steam-methane reforming (SMR) process. Finally, the economic feasibility of the process was evaluated based on the corresponding CAPEX, OPEX and first-year plant cost per kg of the hydrogen produced. The thermal efficiency of the ICLWS process was improved by 31.1% compared to the baseline (Chemical Looping Water Splitting without heat integration) process. The hydrogen efficiency and the effective efficiencies were also higher by 11.7% and 11.9%, respectively compared to the SMR process. The sensitivity analysis showed that the oxygen carrier–to-methane and -steam ratios enhanced the discharged gas and solid conversions from both the reducer and oxidiser. Unlike for the oxidiser, the temperature of the discharged gas and solids from the reducer had an impact on the gas and solid conversion. The economic evaluation of the process indicated hydrogen production costs of $1.41 and $1.62 per kilogram of hydrogen produced for Fe-based oxygen carriers supported by ZrO2 and MgAl2 O4, respectively - 14% and 1.2% lower for the SMR process H2 production costs respectively. Highlights: The process H2 efficiency is improved by 11.7% compared to steam methane reforming. The process effective efficiency is 11.9% higher than to steam methane reforming. The process has carbon intensity of 0.84 kg CO2 per Nm 3 of H2 produced. Oxygen carrier to fuel/steam ratio affects the process reactors conversions. The H2 production cost of the process is 14% lower than steam methane reforming.